The (economic) impacts of climate change: Some implications for Asian economies - Maximilian Auffhammer (Asian Development Bank Institute (ADBI), 2019)
This paper provides an overview of how economists think about climate change impacts with a focus on Asia. It is designed to discuss the steps along the causal chain from physical impacts to impacts on human and natural systems. It starts with a summary of the projected physical impacts of climate change on Asia based on the IPCC's 5th assessment report. It then discusses the concept of the social cost of carbon and how integrated assessment models are used to obtain estimates of this number. This includes a discussion of how a mapping from physical climate impacts to economic damages - called the damage function - is obtained. A recent literature using a mapping of weather/climate into GDP growth rates is discussed, including impact estimates from the literature. The second part of the paper contains an extensive discussion of the mitigation challenge, both physical and economic and concludes with a discussion of the policy challenges going forward.
Keywords: Q54; 330; climate change; economic damages; carbon mitigation